2020
DOI: 10.4236/jss.2020.811023
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Saudi Mothers’ Awareness of Sustainable Children’s Clothing

Abstract: A mother begins to care about her baby once she learns about her pregnancy. She becomes even more concerned about her baby after delivery, and, therefore, starts to scrutinize everything that is of interest to the baby, including the selection of adequate clothing that is not harmful to sensitive skin. Given the importance of providing comfortable and healthy clothing to our children, it was necessary to focus on the type of fabrics from which children's dresses are made. Also there has been a need to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…It is seen in Figure 3-bottom that recycled polyester fabric sample has considerable high tensile strength as compared to organic cotton fabric sample which is in line with Gizem and Kenan [19]. However, Mahjoub et al [8] found that 100% organic cotton fabric offers less tensile resistance due to the lower strength of cotton fibres. Tensile strength depends mainly on the properties of fibre, yarn and fabric.…”
Section: Mechanical Test -Tensile Strength Testsupporting
confidence: 60%
See 1 more Smart Citation
“…It is seen in Figure 3-bottom that recycled polyester fabric sample has considerable high tensile strength as compared to organic cotton fabric sample which is in line with Gizem and Kenan [19]. However, Mahjoub et al [8] found that 100% organic cotton fabric offers less tensile resistance due to the lower strength of cotton fibres. Tensile strength depends mainly on the properties of fibre, yarn and fabric.…”
Section: Mechanical Test -Tensile Strength Testsupporting
confidence: 60%
“…It is extremely tear-resistant compared to other types of fabric. For example, organic cotton twill is resistant to wrinkles, creases and shows less dirt and stains [8]. Hence, choosing fabrics made of eco-fibres assist to achieve design purposes in multifunctional children's clothing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the practical considerations of growth, purchasing children's clothing also carries significant emotional value and concern. Berry et al [59] highlight that the consumption behaviour of children's products reflects the societal values placed by par-ents. This motivates parents to pay meticulous attention to their children's needs and be discerning in selecting clothes that suit them.…”
Section: The Role Of Designers In Functional Children's Fashionmentioning
confidence: 99%
“…Moreover, the satisfaction of the children's clothing market is primarily evaluated for its appearance, function, price, durability, and comfort at first sight. On the other hand, with regards to sustainable clothing products for children, Berry et al (2020) mentioned that parents choose organic cotton clothes because of the quality and better tactile feel which is important for children. Likewise, Gam et al (2010) research framework demonstrated how mothers' environmental concerns, environmental purchasing and recycling behaviour all have a significant impact on their involvement in children's clothing.…”
Section: Children's Clothing Disposal and Sustainable Purchasing Factorsmentioning
confidence: 99%